2010
DOI: 10.1002/bit.22670
|View full text |Cite
|
Sign up to set email alerts
|

Microarray and proteomics expression profiling identifies several candidates, including the valosin‐containing protein (VCP), involved in regulating high cellular growth rate in production CHO cell lines

Abstract: A high rate of cell growth (micro) leading to rapid accumulation of viable biomass is a desirable phenotype during scale up operations and the early stages of production cultures. In order to identify genes and proteins that contribute to higher growth rates in Chinese hamster ovary (CHO) cells, a combined approach using microarray and proteomic expression profiling analysis was carried out on two matched pairs of CHO production cell lines that displayed either fast or slow growth rates. Statistical analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 75 publications
1
57
0
Order By: Relevance
“…In the case of the proteasome, we only find Psmd3 (Rpn3), a structural component of the lid of the 26S proteasome, significantly changing (q<0.05) with increasing qP. Such a general trend towards down-regulation of the structural genes of the proteasome [50,60,61] or related ubiquitin ligases [7] has also been found in previous studies, and was also identified in recombinant yeast [62]. In combination with the results for the ER it seems that, although the ER is upregulated for high protein cargo, in the high producing subclones this is not happening under stress response.…”
Section: Proteasomementioning
confidence: 71%
“…In the case of the proteasome, we only find Psmd3 (Rpn3), a structural component of the lid of the 26S proteasome, significantly changing (q<0.05) with increasing qP. Such a general trend towards down-regulation of the structural genes of the proteasome [50,60,61] or related ubiquitin ligases [7] has also been found in previous studies, and was also identified in recombinant yeast [62]. In combination with the results for the ER it seems that, although the ER is upregulated for high protein cargo, in the high producing subclones this is not happening under stress response.…”
Section: Proteasomementioning
confidence: 71%
“…Five of these genes were selected as engineering targets to analyze their effect on cell densities for mAb-producing CHO K1 cells: valosincontaining protein (VCP), enolase 1 (ENO), heat shock 27-kDa protein 1 (HSPB1), BiP and actin-related protein (ACTR1A). VCP, ENO, HSPB1, and BiP were up-regulated at the protein level, while ACTR1A was down-regulated [12].…”
Section: Enhancing Proliferationmentioning
confidence: 99%
“…To identify relevant targets for cellular engineering, Doolan et al [12] used transcriptomics and proteomics to compare two pairs of CHO cell lines with different growth rates: two antibody-producing CHO K1 cell lines with growth rates of 0.014 and 0.035/h; and two untransfected CHO DUKX cell lines with growth rates of 0.024 and 0.042/h. Using custom-made WyeHamster2a oligo microarrays, the authors identified 118 differentially expressed genes (fold change (FC) ≥ 1.2) common to both pairs of fast-and slow-growing cells [12]. Proteomic analysis (2D difference gel electrophoresis (2D DIGE), matrix-assisted laser desorption/ionization-time-of-flight (MALDI-TOF)-MS and LC-MS/MS) revealed 34 differentially regulated protein spots (FC ≥ 1.5) in the antibody-producing CHO K1 pair, and 24 in the untransfected CHO DUKX pair.…”
Section: Enhancing Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…The microarray has been used to study the effects of overexpression of soluble PACE on CHO cells expressing a transgene for bone morphogenic protein-2 (Doolan et al 2008), predicting productivity in CHO (Clarke et al 2011), as well as to identify genes linked with the ability of CHO cells to modulate their rate of growth (Doolan et al 2010). …”
Section: Introductionmentioning
confidence: 99%